Leukoaraiosis predicts hidden global functioning impairment in nondisabled older people: the LADIS (Leukoaraiosis and Disability in the Elderly) Study - Pantoni, Leonardo; Poggesi, Anna; Basile, Anna Maria; Pracucci, Giovanni; Barkhof, Frederik; Chabriat, Hugues; Erkinjuntti, Timo; Ferro, José M.; Hennerici, Michael G.; O'Brien, John; Schmidt, Reinhold; Visser, Marieke C.; et al. (Journal of the American Geriatrics Society, 2006)
OBJECTIVES: To determine whether leukoaraiosis severity is independently associated with differences in global functioning in nondisabled elderly patients. - DESIGN: Cross-sectional data analysis from an ongoing longitudinal multicenter and multinational study. - SETTING: The Leukoaraiosis and Disability Study, a collaboration aimed at assessing leukoaraiosis as an independent predictor of the transition to disability in older people. - PARTICIPANTS: Six hundred thirty-nine nondisabled subjects (288 men, 351 women, mean age+/-standard deviation 74.1+/-5.0) with magnetic resonance imaging-detected leukoaraiosis of different severity and presenting with one of the following: mild cognitive or motor disturbances, minor cerebrovascular events, or mood alterations or in whom leukoaraiosis was incidentally identified. - MEASUREMENTS: Centralized assessment of leukoaraiosis severity according to the three severity degrees of the Fazekas scale; Disability Assessment for Dementia (DAD) Scale for measurement of global functioning. - RESULTS: At baseline, 44% of participants had a mild, 31% a moderate, and 25% a severe degree of leukoaraiosis. A significant trend toward declining performance on the DAD Scale was apparent with increasing leukoaraiosis score severity (total score=98.8, 98.6, 97.5, respectively, in the three leukoaraiosis categories, analysis of variance P=.002). Similar trends were obtained for basic (P=.01) and instrumental (P<.001) function items. The statistical significance of these differences was confirmed in a multiple linear regression analysis correcting for numerous factors known to influence disability in older people. Executive function test performance declined along with increasing leukoaraiosis severity and was significantly related to DAD total score. - CONCLUSION: Even in nondisabled elderly patients, levels of functional ability are related to white matter lesion severity. Executive dysfunction may mediate this relationship.
Gesehen am 06.05.2022